Allergic Contact Dermatitis Caused By Daily Soap Products: One Case Report - Shelly Lavenia Sambodo; Suci Widhiati (International Journal Labs, 2025)
Allergic contact dermatitis (ACD) is a skin disorder resulting from contact with an allergenic substance. Most cases of ACD are caused by cosmetic ingredients and daily-use products. We report a case of ACD caused by sodium lauryl sulfate (SLS) and fragrance in soap, confirmed by positive patch test results. A 29-year-old woman with chronic persistent itching that did not improve with medication presented to the Dermatovenereology Outpatient Clinic of Dr. Moewardi Hospital. She had a history of using virgin coconut oil (VCO) and various handwashing soaps. Dermatological examination revealed multiple erythematous macules with overlying scales and xerotic skin, suggestive of ACD. The patient underwent a patch test with standard materials as well as personal products she brought to confirm the diagnosis. The patch test showed a positive allergic reaction to Sunlight® liquid soap, Biore® liquid soap, Cerianerss® lychee-flavored VCO, One Scrub Onemed® 4%, and Paquito® liquid soap. Patch testing is an important and useful tool for diagnosing ACD. Although the procedure is simple, it requires several days for evaluation. In this case, we identified the products responsible for ACD in our patient and advised her to avoid them. Several substances with allergenic potential were identified by comparing product compositions with patch test results. However, these findings could not determine which specific compounds were allergenic. Hence, further patch testing of individual compounds is necessary.